Stress in families with intellectually disabled child - Keskinova, Angelka; Chichevska Jovanova, Natasha; Ajdinski, Goran (Faculty of Philosophy, Skopje, 2014)
Being a parent of an intellectually disabled child is often associated with a range of problems in the mental health, with increased levels of stress, a feeling of inferiority and shame, decreased physical function, fatigue and exhaustion parents. As a result of increased care requirements, it is reasonable to assume that parents of intellectually disabled children are at increased risk for developing high levels of personal stress. In recent decades, the overall treatment of these people is completely changed. Medical and institutional approach focus move to integral rehabilitation, which includes the entire family and their needs. The aim of our study was to establish the level of stress and stressful situations which pass the family of a child with intellectual disability in everyday functioning. In order to achieve the goal we set the following tasks: determining the level of stress faced by the family as well as determining the existing formal and informal support groups, their activity and function. The survey covered 104 families who have a child with an intellectual disability. We used the descriptive method and the method of generalization. Through the data analysis we came to the conclusion that 90.38% of families experienced their first stress and shock when they found out that their child has an intellectual disability. Most of them (60.58%) saw it as an extreme stress. This stressful situation is believed to be the first, but further stress doesn’t disappear. The parents are exposed to constant stress in their everyday activities, which is caused by the child’s needs and by the attitudes of the environment.
Стресот во семејство со дете со интелектуална попреченост
Keywords: stress, family, intellectually disabled children